(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Various medication regimens have been used to eradicate Helicobacter pylori in dialysis patients; however, optimal response to treatment is still a challenge. This study aimed to compare response to H pylori eradication in dialysis and nonuremic patients. Materials and Methods. In a randomized controlled trial, dialysis patients with dyspepsia and confirmed positive endoscopic biopsy for H pylori were compared to nonuremic patients. Participants were randomly assigned to receive clarithromycin or levofloxacin. H pylori eradication was assessed using stool antigen test 4 weeks later. Results. Forty-four dialysis and 44 nonuremic patients participated in the study. Four dialysis patients and 2 nonuremic patients did not respond to levofloxacin (P = .35). Six dialysis patients and 4 nonuremic patients did not respond to clarithromycin (P = .47). Conclusions. Response rate to H pylori eradication by clarithromycin and levofloxacin was slightly lower in dialysis patients compare to nonuremic patients. In dialysis patients, response rate to levofloxacin was slightly higher than clarithromycin, but the results were not significantly different.